HIV and AIDS: Knowledge, attitudes and practices of counsellors at NGOs in Emfuleni Municipality - Mutasa, Daniel (My University, 2018)
Human Immunodeficiency Virus (HIV), which leads to Acquired Immune Deficiency Syndrome (AIDS), is one of the world’s greatest health threats and leads to death of millions of people. In 2016, an estimated one million people died of AIDS related causes globally. An estimated 36,7 million people in the world are living with HIV and AIDS. HIV counselling is regarded an integral part of prevention and coping strategies and an effective tool in preventing the spread of HIV and AIDS. HIV and AIDS have negative psycho-social effects to individuals and families. This study investigated counsellor’s knowledge of HIV and AIDS, attitudes towards PLWHA and counselling practices at Non-Governmental Organization (NGOs) operating within Emfuleni Local Municipality. Incorrect knowledge of HIV and AIDS, negative attitudes towards PLWHA and poor practices can negatively affect efforts to curb the pandemic. A non -experimental study was conducted with a sample of 101 HIV counsellors. Data was gathered by a self - administered questionnaire soliciting counsellors responses pertaining to knowledge of HIV and AIDS, attitudes towards PLWA and counselling practices. Data was analysed quantitatively utilising the Statistical Package for Social Scientists (SPSS). A statistical analysis was done to test the significance of relationship between knowledge of HIV and AIDS, attitudes towards PLWA and practices utilizing the demographics of the study group. The majority of respondents 86(84,8%) had good knowledge of HIV and AIDS. There were no significant relationships (P>0,05) between age, race, marital status, qualifications, years of experiences and respondents’ level of knowledge. Attitudes towards PLWHA (87,16%) were positive and were not statistically significantly correlated with HIV and AIDS knowledge and counselling practices. There were significant relationships between qualifications and counselling practices (F = 4,335, P= 0,003).
A research report submitted to the Faculty of Human and Community Development, University of Witwatersrand in partial fulfilment of the requirements for the degree of Masters of Arts in the field of Social Development, 2018